A comprehensive study on novel alumino-borosilicate glass reinforced with Bi2O3 for radiation shielding applications: synthesis, spectrometer, XCOM, and MCNP-X works - Kurtulus, Recep; Kavas, Taner; Akkurt, Iskender; Gunoglu, Kadir; Tekin, H. O.; Kurtulus, Cansu (Journal of materials science. Materials in electronics, 2021)
In the present work, a novel glass system, 10Na 2 O–6MgO–9CaO–5Al 2 O 3 –12B 2 O 3 -(100− x )SiO 2 – x Bi 2 O 3 ( x : 0, 2.5, 5, 7.5, and 10 mol%), was investigated in terms of physical properties and radiation shielding competencies. For this, the ABS glass series was successfully synthesized by following batch preparation, melting, shaping, and annealing steps. Mineralogical analysis X-ray diffraction (XRD) and glass density ( ρ glass ) were measured, while molar volume ( V m ) and oxygen packing density (OPD) calculations were done for each glass series. We determined that the increasing amount in Bi 2 O 3 in substitution for SiO 2 ascended the overall ρ glass from 2.8067 to 3.3067 g/cm 3 . Further, one can report that V m and OPD exhibited an opposite behavior due to the loose packing in the glass network. The XRD patterns clearly indicated the non-crystallinity in the ABS series irrespective of the varying amounts in Bi 2 O 3 . On the other hand, gamma-ray spectroscopic measurements were performed in the photon energies of 0.662, 1.173, and 1.332 MeV to find out mass attenuation coefficient (MAC). It was observed that the highest MAC value was obtained for ABS4 glass (highest Bi 2 O 3 content). Additionally, Monte Carlo simulation codes (MCNP-X) were employed to highlight the MAC values. As a result of these determinations, we reported that the experimental, XCOM, and MCNP-X findings demonstrated a good agreement with each other. Based on the experimental MAC, other significant parameters, such as the half-value layer (HVL), tenth-value layer (TVL), effective atomic numbers ( Z eff ), and Exposure Build-up Factors (EBF) and Energy Absorption Build-up Factors (EABF) were evaluated for the investigated ABS glass system.